Associations of loneliness with mental health and with social and physical activity among university students in Germany: results of the COVID-19 German student well-being study (C19 GSWS) - Wenig, Vanessa; Heumann, Eileen; Stock, Christiane; Busse, Heide; Negash, Sarah; Pischke, Claudia R.; Heinrichs, Katherina (Frontiers in Public Health, 2023)
Introduction University students are at high risk for loneliness with a potential negative impact on health. The COVID-19 measures disrupted students’ academic routine and social life, which might have affected their perception of loneliness. This study investigated the prevalence of perceived loneliness among university students in Germany during the COVID-19 pandemic and its associations with mental health, behavioral outcomes, and sociodemographic characteristics. Methods COVID-19 German student well-being study (C19 GSWS) collected data from five German universities from October 27th to November 14th, 2021, resulting in a sample of 7,203 respondents. Associations of loneliness with depressive symptoms, anxiety, social and physical activity, as well as sociodemographic characteristics, were analyzed using multivariable logistic regressions. Results A total of 20.6% of students reported loneliness. Students with depressive or anxiety symptoms had more than eight- or sixfold odds, respectively, for reporting loneliness (depressive symptoms: OR = 8.29; 95% CI: 7.21–9.52; anxiety: OR = 6.48; 95% CI: 5.65–7.43) compared with students who did not report any symptoms. Students who were less physically active were more likely to experience loneliness compared with students who were more physically active (no moderate physical activity: OR = 1.39; 95% CI: 1.21–1.59; no vigorous physical activity: OR = 1.19; 95% CI: 1.04–1.36). We found no association between loneliness and social activity. However, loneliness was associated with being single (OR = 2.93; 95% CI: 2.55–3.36), living alone (OR = 1.31; 95% CI: 1.13–1.52), or having a temporary residency status in Germany (OR = 2.24; 95% CI: 1.65–3.04). Conclusion Our findings highlight the importance of loneliness as a relevant factor associated with health. Further research is needed to determine potential protective factors to tackle loneliness and to investigate how study conditions at higher education institutions may affect students’ perceived loneliness.